IS WHAT YOU PREFER WHAT YOU DO? REPRESENTATIONS IN DEFINITE INTEGRAL - (:unkn) unknown (INT GRP PSYCHOL MATH EDUC, 2011)
In the process of problem solving, being able to select and use the appropriate representation affects performance. Hence, the representations preferred and used in the process of solving definite integral problems and the consistency between these two were investigated. This research is a case study within the qualitative interpretive paradigm. The participants were 45 second year teacher trainees studying mathematics education at a state university. The Representation Preferences and Transition Test was administered to the trainees and it was analyzed descriptively. The findings indicated that teacher trainees lacked sufficient levels of representation awareness in the process of solving definite integral problems. The most preferred and used representation type in the problem solving process was algebraic representation. However, there was inconsistency between the representation types that were preferred and used. We discuss the findings in light of the literature and propose several suggestions to increase success at problem solving.